Release and establishment in Nigeria of Epidinocarsis lopezi, a parasitoid of the cassava mealybug, Phenacoccus manihoti - Lema, K.M.; Herren, H.R. (1985)
The encyrtid wasp Epidinocarsis (= Apoanagyrus) lopezi (De Santis) was imported from Paraguay into Nigeria for the biological control of the cassava mealybug, Phenacoccus manihoti Matile‐Ferrero. It was mass‐reared and released at four localities in Nigeria. The parasitoid is now established and it is dispersing throughout cassava growing areas of Nigeria.